Negative pressure wound therapy for skin necrosis prevention after snakebite in the emergency department: A retrospective cohort study. Issue 3 (22nd January 2021) - Kim, Kwan Jae; Min, Jin Hong; Yoo, Insool; Kim, Seung Whan; Lee, Jinwoong; Ryu, Seung; You, Yeon Ho; Park, Jung Soo; Jeong, Won Joon; Cho, Yong Chul; Oh, Se Kwang; In, Yong Nam; et al.
Abstract : Abstract: This retrospective cohort study aimed to compare the effectiveness of conventional treatment and ultra-early application of negative pressure wound therapy (NPWT) in patients with snakebites. Patients who visited the emergency department within 24 hours after a snakebite were assigned to the non- NPWT or NPWT group. Swelling resolution time and rates of necrosis, infection, and operations were compared between the 2 groups. The Stony Brook Scar Evaluation Scale was used to measure short- and long-term wound healing results. Among the included 61 patients, the swelling resolution time was significantly shorter in the NPWT group than in non- NPWT group ( P  = .010). The NPWT group showed lower necrosis (4.3% versus 36.8%; P  = .003) and infection (13.2% and 4.3%; P  = .258) rates than the non- NPWT group. The median Stony Brook Scar Evaluation Scale scores were higher in the NPWT group than in the non- NPWT group ( P < .001). These findings suggest that ultra-early application of NPWT reduces edema, promotes wound healing, and prevents necrosis in patients with snakebites.